Factors Influencing the Role of Religious Leaders in the Process Accelerate Stunting Response in East Nusa Tenggara Province - Picauly, Intje; Adi, Anak Agung Ayu Mirah; Meiyetriani, Eflita; Mading, Majematang; Weraman, Pius; Nashriyah, Siti Fadhilatun; Hidayat, Ahmad Thohir; Boeky, Daniela L. Adeline; Lobo, Varry; Saleh, Asmulyati S.; Peni, Jane A. (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Stunting was the impact of chronic malnutrition in the long term and has an impact on children's growth and development disorders. Stunting has become a priority for the Indonesian government, including in the Province of East Nusa Tenggara with a stunting reduction target of 14% in 2024. The Indonesian governments have made many efforts to overcome stunting. Religious leaders are parties suspected of being able to play a role in the process. This study was aimed to determine the factors that influence the role of religious leaders in supporting the process of accelerating stunting reduction in the dry land area in East Nusa Tenggara. Subjects and Method: This was a mixed-method study. This study was conducted in May 2022 using the focus group discussion (FGD) method and involved 13 religious leaders who were taken purposively. The data collected were analyzed qualitatively (making interview transcripts) and quantitatively. The independent variables were level of understanding about stunting, support for policies/programs related to stunting, stunting program budget support, national program support: CATIN facilitation, and cross-sectoral cooperation support. The statistical analysis used is multiple logistic regression analysis. Results: Factors that significantly influence the role of religious leaders are the level of understanding of religious leaders about stunting (aOR= 3.50; 95% CI= 0.12 to 12.3; p= 0.010) and support factors for cross-sectoral cooperation (aOR= 2.00; 95% CI= 1.22 to 21.10; p= 0.007). Budget support for stunting related policies/ program (aOR= 2.40; 95% CI= 1.76 to 12.32; p= 0.621), support policy/ program related to stunting (aOR= 1.70; 95% CI= 1.27 to 7.32; p= 0.387), and national program, support “CATIN Mentoring” (aOR= 1.10; 95% CI= 0.37 to 21.02; p= 0.621) were statistically non-significant. Conclusion: Factors that influence the role of religious leaders were the level of understanding of religious leaders about stunting, support factors for cross-sectoral cooperation, budget support for stunting related policies, support policy related to stunting national program, and support “CATIN Mentoring”. Keywords: the role of religious leaders, acceleration of stunting prevention, chronic malnutrition. Correspondence:Intje Picauly, Department of Nutrition, Faculty of Public Health, Universitas Nusa Cendana. Jl. Adi Sucipto Penfui, Kupang, East Nusa Tenggara, Indonesia. Mobile: +62822-3714-5517. Email: intjepicauly@staf.undana.ac.id.